Synthesis of 4-Aryl-3-ethoxycarbonyl-1-oxo-1,2,3,4-tetrahydronaphthalene: An Imporant Frame Work in Lignan Family - Singh, Ashok Kumar (Journal of Nepal Chemical Society, 2012)
4,4-diaryl-3-ethoxycarbonyl-3-butenoic acid (2a-d, Scheme 1) has been synthesized by Stobbe condensation of substituted benzophenones 1a-d with t-potassium butoxide and diethyl succinate. Compounds 2a-d on reduction with sodium amalgum furnished 4,4-diaryl-3-ethoxycarbonyl-3-butanoic acid 3a-d, which on intramolecular cyclization with polyphosphoric acid gave target compounds 4-aryl-3-ethoxycarbonyl-1-oxo–1,2,3,4-tetrahydronaphthalene 4a-d. DOI: http://dx.doi.org/10.3126/jncs.v27i1.6666 J. Nepal Chem. Soc., Vol. 27, 2011 86-93